Proceedings of the 20th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval - SIGIR 1997
DOI: 10.1145/258525.258601
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting clustering and phrases for context-based information retrieval

Abstract: This paper explores exploiting the synergy between document clustering and phrasal analysis for the purpose of automatically constructing a corrrex~-busedretrieval system. A contex~consists of two components -a cluster of logically related articles (its exrension) and a small set of salient concepts, represented by words and phrases and organized by the cluster's key terms (its irr~ertsion). At inn-time, the system presents contexts that best match the result list of a user's natural language query. The user c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…The most profound extension of the present study from former visualization studies is therefore the novel step of natural language parsing of noun phrases from the citation contexts. The rationale for the use of noun phrases as key conceptual phrases is that they represent more meaningful concepts than individual words (e.g., ANICK & VAITHYANATHAN, 1997). Noun phrases are believed to be content bearing units and thus good indicators of the content of a text.…”
mentioning
confidence: 99%
“…The most profound extension of the present study from former visualization studies is therefore the novel step of natural language parsing of noun phrases from the citation contexts. The rationale for the use of noun phrases as key conceptual phrases is that they represent more meaningful concepts than individual words (e.g., ANICK & VAITHYANATHAN, 1997). Noun phrases are believed to be content bearing units and thus good indicators of the content of a text.…”
mentioning
confidence: 99%
“…Phrase indexing has been studied by many previous studies (Gutwin et al 2003;Fagan 1989;Anick and Vaithyanathan 1997;Arampatzis et al 1998). These studies have shown that phrase indexing can improve retrieval effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Because document keyphrases as described in our study are a subset of a document's noun phrases, it is very possible that keyphrases can also be used in the same applications of noun phrases and better results may be acquired. Many studies utilizing noun phrases focus on the applications of retrieval systems and browsing interfaces (Liddy and Myaeng 1993;Anick and Tiperneni 1999;Inf Retrieval (2008) 11:229-249 231 Wacholder et al 2001Arampatzis et al 1998); some others explore their applicatuions on document classification and clustering (Anick and Vaithyanathan 1997;Zamir and Etzioni 1999). Anick and Vaithyanathan (1997) describe a model of context-based information retrieval.…”
Section: Applications Of Keyphrasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizing text collections for enabling the retrieval by content [2,14,15,16] and searching [4] can be accomplished by using text collection clustering. Cutting et al used a clustering technique that supports an iterative searching interface by dynamically scattering a document collection into smaller semantic clusters.…”
Section: Text Clustering For Ir By Contentmentioning
confidence: 99%